PAZ6 Cells Constitute a Representative Model for Human Brown Pre-Adipocytes - Kazantzis, Melissa; Takahashi, Virginia; Hinkle, Jessica; Kota, Smitha; Zilberfarb, Vladimir; Issad, Tarik; Abdelkarim, Mouaadh; Chouchane, Lotfi; Strosberg, Arthur Donny (Frontiers in Endocrinology, 2012)
The role of brown adipose tissue (BAT) in human metabolism and its potential as an anti-obesity target organ have recently received much renewed attention. Following radiological detection of substantial amounts of BAT in adults by several independent research groups, an increasing number of studies are now dedicated to uncover BAT’s genetic, developmental, and environmental determinants. In contrast to murine BAT, human BAT is not present as a single major fat depot in a well-defined location. The distribution of BAT in several areas in the body significantly limits its availability to research. A human brown adipocyte cell line is therefore critical in broadening the options available to researchers in the field. The human BAT-cell line PAZ6 was created to address such a need and has been well characterized by several research groups around the world. In the present review, we discuss their findings and propose potential applications of the PAZ6 cells in addressing the relevant questions in the BAT field, namely for future use in therapeutic applications.